Essentials of anatomy & physiology - Seeley, Rod R. (McGraw-Hill, 2005)
Designed for the one-semester course, Seeley et al.'s Essentials of Anatomy and Physiology is written to allow instructors the ability to accomplish one overall goal: to teach the basics of A&P while fostering the skill of problem solving. Through learning how to solve problems and think critically, students learn A&P based on two themes: the relationship between structure and function, and homeostasis.